Situation Report: Hungary, 7 August 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Minister of Public Education Hungarians at East Berlin Youth Festival The Problem of Choosing a Career Hungary to Build Autobahnen with Help of Western Enterprises Party Organization in Red Star Tractor Factory Faces "Difficult Test" Hungary Admitted to GATT Hungary: A Grain Exporting Country? Growing Interest in Achievements of US Agriculture Increased Rapprochement toward Hungarians Living Abroad: Second Mother Tongue Conference